2006
DOI: 10.1159/000092712
|View full text |Cite
|
Sign up to set email alerts
|

Th2-Cell-Mediated Chemokine Synthesis Is Involved in Allergic Airway Inflammation in Mice

Abstract: Eosinophilic inflammation in the bronchial mucosa has been recognized as a prominent pathological feature of bronchial asthma. Th2 cells have been implicated in the local infiltration and activation of eosinophils. The migration of eosinophils as well as Th2 cells is controlled by chemokines, suggesting a crucial role of chemokines in the pathogenesis of bronchial asthma. To elucidate the mechanism by which Th2 cells induce eosinophilic inflammation, a Th2-cell-dependent murine model of asthma was employed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…However, the results are still controversial and the potential efficacy of CCR4 blockers in allergic disorders associated with eosinophilic inflammation remains unclear. We have generated an allergic airway inflammation model in which mice are transferred with in vitro-polarized OVA-specific Th1, Th2, or Th17 cells and challenged with OVA [26][27][28]. We have generated an allergic airway inflammation model in which mice are transferred with in vitro-polarized OVA-specific Th1, Th2, or Th17 cells and challenged with OVA [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the results are still controversial and the potential efficacy of CCR4 blockers in allergic disorders associated with eosinophilic inflammation remains unclear. We have generated an allergic airway inflammation model in which mice are transferred with in vitro-polarized OVA-specific Th1, Th2, or Th17 cells and challenged with OVA [26][27][28]. We have generated an allergic airway inflammation model in which mice are transferred with in vitro-polarized OVA-specific Th1, Th2, or Th17 cells and challenged with OVA [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…The model has provided relatively consistent and reproducible results and thereby enables us to easily evaluate the efficacy of antibodies and chemical compounds [26][27][28]. The model has provided relatively consistent and reproducible results and thereby enables us to easily evaluate the efficacy of antibodies and chemical compounds [26][27][28].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Reduced eotaxin-1 levels in the lungs of allergen-challenged Gal-3 KO mice may be due to reduced infiltration of the airways by inflammatory cells that release eotaxin-1 such as Th2 cells, alveolar macrophages and/or eosinophils themselves, or due to decreased IL-13-induced production of this chemokine by lung cells. Chemokines synthesized by Th2 cells and other cell types are involved in the development of eosinophilic inflammation in bronchial asthma and studies using a Th2-cell-dependent murine model of asthma have shown that infiltration of eosinophils and antigen-specific Th2 cells is associated with eotaxin, MCP-3, RANTES and MCP-1 in the lungs of Th2-cell-transferred mice after antigen provocation (49). In the present study, in addition to eotaxin-1, expression of MCP-1 in the lung tissue of chronic allergen-challenged Gal-3 KO mice was also inhibited (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Non-sensitized mice, despite the strong Th1 response elicited by exposure to S. pneumoniae, had comparable (IL-4 and IL-5) or higher levels (IL-10 and IL-13) of Th2 cytokines and chemokines associated with airway inflammation (e.g. RANTES and eotaxin) [42,43] compared with sensitized mice. These data suggest that mice sensitized with OVA might not have the expected classic Th2 immune responses and non-sensitized mice might have undiminished Th2 responses for unknown reasons.…”
Section: Discussionmentioning
confidence: 99%